The Impact of Prior Activity History on the Influence of Restricted Repetitive Behaviors on Socialization for Children With High-Functioning Autism. Issue 1 (January 2018) - Koegel, Robert L.; Oliver, Kelsey; Koegel, Lynn K.
Research has demonstrated that incorporating restricted interests of an individual with autism into recess activities is effective at increasing socialization with typically developing peers. However, certain activity contexts may alter the reinforcing influence of the restricted repetitive behaviors (RRBs) depending on an individual's history in that activity. Using an alternating treatment design, this study examined whether an individual's history with an activity affected socialization. RRBs were embedded into activities with a reported positive history (i.e., prior history of positive experiences) and activities with a reported negative history (i.e., prior history of aversive experiences) for participants. Data indicated that socialization increased and remained above baseline levels when RRBs were introduced during activities with a positive history, whereas socialization was minimal when RRBs were introduced in activities with a negative history. Social significance and implications for designing activities that incorporate a child's RRBs are discussed.